2023
DOI: 10.3389/fnut.2023.1131126
|View full text |Cite
|
Sign up to set email alerts
|

Association between the prudent dietary pattern and blood pressure in Chinese adults is partially mediated by body composition

Abstract: High blood pressure or hypertension is one of the major risks of cardiovascular disease, which is the leading cause of death in China. This study aimed to assess the relationship between dietary patterns and blood pressure among Chinese adults. Using factor analysis of 66-item food frequency questionnaire to identify dietary patterns. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured according to standardized guidelines. Multivariate linear regressions were performed in 6849 Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…We found a positive association between the "Western Pattern" and CircS and an inverse association between the "Prudent Pattern" and CircS among older adults. Our findings are consistent with the reported inverse and positive associations for "Prudent/Healthy Patterns" and "Western/Unhealthy Patterns", respectively, with MetS and its components [16,[35][36][37][38][39][40], CVDs [41,42], sleep [43], and depression [44]. A meta-analysis distilled evidence from forty observational studies and concluded that the "Healthy Pattern" was associated with lower odds of MetS (OR = 0.85, 95% CI 0.79-0.91), while the "Meat/Western Pattern" was associated with higher odds of MetS (OR = 1.19, 95% CI 1.09-1.29) [16].…”
Section: Discussionsupporting
confidence: 92%
“…We found a positive association between the "Western Pattern" and CircS and an inverse association between the "Prudent Pattern" and CircS among older adults. Our findings are consistent with the reported inverse and positive associations for "Prudent/Healthy Patterns" and "Western/Unhealthy Patterns", respectively, with MetS and its components [16,[35][36][37][38][39][40], CVDs [41,42], sleep [43], and depression [44]. A meta-analysis distilled evidence from forty observational studies and concluded that the "Healthy Pattern" was associated with lower odds of MetS (OR = 0.85, 95% CI 0.79-0.91), while the "Meat/Western Pattern" was associated with higher odds of MetS (OR = 1.19, 95% CI 1.09-1.29) [16].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the Healthy-Economic DP had a reduced caloric contribution (2624 kcal/day) while exhibiting the highest intake of polyunsaturated fatty acids (22.65 g/day, p = 0.001) and total dietary cholesterol (383.52 mg/day, p = 0.01) ( Table 3 ). The healthy DP, also known as prudent, has been commonly described in various populations [ 29 , 30 , 31 ] and has been associated with the prevention of CVD and MetS [ 7 , 24 ]. However, in the present results, the adherence to this DP did not show an association with a lower prevalence of overweight or obesity.…”
Section: Discussionmentioning
confidence: 99%